1995
DOI: 10.1093/treephys/15.4.267
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cold storage and water stress on water relations and gas exchange of white spruce (Picea glauca) seedlings

Abstract: To determine the effects of lifting time and storage on water-stress resistance of nursery-grown white spruce (Picea glauca (Moench) Voss) seedlings, we compared gas exchange, water relations and mortality of 3-year-old seedlings lifted in October 1991 and stored at -2 degrees C for 3 months with seedlings lifted in January 1992. The seedlings were placed in nutrient solution and subjected to -1.1 or -2.7 MPa water stress induced by polyethylene glycol 3350 for 9 days. Water stress, but not lifting time, had a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

1997
1997
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 39 publications
0
21
0
1
Order By: Relevance
“…It has been demonstrated that sugars and starch can be reduced during storage [7], and this reduction jeopardizes stress resistance and consequently post-planting survival [17]. McCracken [22] found evidence that this depletion was particularly noticeable in radiata pine seedlings during cold storage.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that sugars and starch can be reduced during storage [7], and this reduction jeopardizes stress resistance and consequently post-planting survival [17]. McCracken [22] found evidence that this depletion was particularly noticeable in radiata pine seedlings during cold storage.…”
Section: Discussionmentioning
confidence: 99%
“…Since the frozen storage of spring planted seedlings is usually initiated in October, prolongation would account for a storage period of over 30 weeks. Long storage periods may, however, affect the postplanting performance, especially if seedlings are exposed to water stress after planting [12,16,17]. In addition, dormant seedlings initiating new growth after planting allocate preferentially more photosynthates to shoot growth compared to root growth [8], which may reduce the ability to maintain balanced seedling water relations when exposed to drought.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast with seedlings of deciduous tree species, coniferous seedlings are able to photosynthesise in mild late winter and early spring conditions [17,19]. Consequently, coniferous seedlings may use both currently produced or stored C sources.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, coniferous seedlings may use both currently produced or stored C sources. The importance of these two sources for new growth can vary by species [24], but several studies have reported that transplanted seedlings are often water-stressed, leading to a reduction in photosynthetic capacity [15,19]. A decrease in C assimilation induces increased mobilization of C reserves to satisfy growth and maintenance metabolism.…”
Section: Introductionmentioning
confidence: 99%